2002
DOI: 10.1152/ajpregu.00369.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactivity in intrapulmonary arteries of chicken embryos during transition to ex ovo life

Abstract: The present study aimed to characterize pulmonary vascular reactivity in the chicken embryo from the last stage of prenatal development and throughout the perinatal period. Isolated intrapulmonary arteries from non-internally pipped embryos at 19 days of incubation and from internally and externally pipped embryos at 21 days of incubation were studied. Arterial diameter and contractile responses to KCl, endothelin-1, and U-46619 increased with incubation but were unaffected by external pipping. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 51 publications
(81 reference statements)
5
52
0
Order By: Relevance
“…Mediators, like catecholamines Hassanzadeh et al, 1997aHassanzadeh et al, , 2001Hassanzadeh et al, , 2002, endothelin-1 (Villamor et al, 2002;Odom et al, 2004), methylglyoxal (Khajali and Fahimi, 2010;Khajali and Wideman, 2011) and serotonin (Chapman and Wideman, 2002;Kluess et al, 2012) play a major role in accelerating of pulmonary hypertension that may lead to ascites in broiler chickens (Hassanzadeh et al, 1997a, b;Wideman et al, 2013).…”
Section: B Mediators Contributed To Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediators, like catecholamines Hassanzadeh et al, 1997aHassanzadeh et al, , 2001Hassanzadeh et al, , 2002, endothelin-1 (Villamor et al, 2002;Odom et al, 2004), methylglyoxal (Khajali and Fahimi, 2010;Khajali and Wideman, 2011) and serotonin (Chapman and Wideman, 2002;Kluess et al, 2012) play a major role in accelerating of pulmonary hypertension that may lead to ascites in broiler chickens (Hassanzadeh et al, 1997a, b;Wideman et al, 2013).…”
Section: B Mediators Contributed To Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Lefkowitz et al (1984) and Cohen et al (1984) reported that the constriction of smooth muscles of the vascular system was a consequence of an adrenergic stimulation due to catecholamine hormones. So, intravenously administered epinephrine elicits immediate pulmonary vasoconstriction accompanied by pulmonary hypertension (Wideman, 1999;Villamor et al, 2002;Lorenzoni and RuizFeria, 2006;Ruiz-Feria, 2009;Bautista-Ortega and RuizFeria, 2010).…”
Section: B Mediators Contributed To Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wnal pH was 7.38-7.42 and pCO 2 was 4.6-5.6 kPa in all solutions. Each DA was stretched to its individual optimal lumen diameter, i.e., the diameter at which it developed the strongest contractile response to 62.5 mM K + , using a diameter-tension protocol as previously described (Agren et al 2007;Villamor et al 2002). During the Wrst phase of stabilization and determination of optimal diameter, DA rings were maintained in KRB buVer with a pO 2 of »3 kPa.…”
Section: Recording Of Arterial Reactivitymentioning
confidence: 99%
“…Chicken embryos have a mammalian-like circulation, with an extraembryonic circuit involved in the gas exchange (the chorioallantois), analogous to the placenta, and they maintain bilaterally developed DA (3). During the past few years, our group has analyzed developmental changes in reactivity of chicken embryo systemic and pulmonary arteries (26,38,51,52). In the present study, we hypothesized that the responsiveness of the chicken embryo DA to O 2 and other vasoconstrictors is developmentally regulated.…”
mentioning
confidence: 97%